2016
DOI: 10.1002/cam4.843
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine CXCL1 may serve as a potential molecular target for hepatocellular carcinoma

Abstract: The purpose of this study was to screen for changes in chemokine and chemokine‐related genes that are expressed in hepatocellular carcinoma (HCC) as potential markers of HCC progression. Total RNA was extracted from tumor and peritumor tissues from mice with HCC and analyzed using a PCR microarray comprising 98 genes. Changes in gene expression of threefold or more were screened and subsequently confirmed by immunohistochemical analyses and western blotting. Furthermore, whether chemokine knockdown by RNA inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…In our study, we found that in hepatocellular carcinoma tumors, several CXCR2 ligands, CXCL1, CXCL2, CXCL5, and CXCL8 showed relatively high expression level. Coincidentally, previous studies reported that abnormally expression of these chemokines was involved in tumor proliferation, invasion, and prognosis of HCC . These findings indicate that CXCR2 ligands may play crucial role in HCC development or tumorigenic maintenance.…”
Section: Discussionmentioning
confidence: 79%
“…In our study, we found that in hepatocellular carcinoma tumors, several CXCR2 ligands, CXCL1, CXCL2, CXCL5, and CXCL8 showed relatively high expression level. Coincidentally, previous studies reported that abnormally expression of these chemokines was involved in tumor proliferation, invasion, and prognosis of HCC . These findings indicate that CXCR2 ligands may play crucial role in HCC development or tumorigenic maintenance.…”
Section: Discussionmentioning
confidence: 79%
“…GROs were initially isolated from the CM of a melanoma cell line (Richmond and Thomas, 1988 ) and their role in promoting tumorigenesis was identified in several tumors. Downregulation of CXCR1 and CXCR2, by interfering siRNA, inhibits melanoma tumor growth and cell invasion (Singh et al, 2010 ); similarly RNAi of GROα suppresses tumor growth in hepatocellular carcinoma (Han et al, 2016 ). In GBM cell lines, GROα promotes tumor growth, in vitro cell motility and invasiveness and enhances tumor cell spread in vivo (Zhou et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Its sensitivity for HCC screening ranges from 41 to 65% at a cutoff of 20 ng/mL . In recent years, various biomarkers have emerged for diagnosing HCC and predicting patient outcome, including glypican 3 and insulin‐like growth factor (IGF)II mRNA , Keap1 and pNrf2 , 3‐microRNA and AFP , CXCL1 , minichromosome maintenance complex ‐7 , and IGF1 receptor , among others.…”
Section: Discussionmentioning
confidence: 99%